The Mind and its Procedure in Buddhism - Ghimire, Chandra Kala (NUTA Journal, 2021)
The mind (nāma) and matter (rūpa) are the two great constituents of the beings. Nāma refers to the mental phenomena of the four aggregates vedanā, saññā, saṅkhāra and vijññān. The mind is a formless, shapeless, non-physical field that functions to store, perceive, and analyze information. It originates when the six senses; eye, ear, nose, tongue, skin and the mind get contact with their corresponding objects; form, sound, smell, taste, touch and mental constituents respectively. The mind and the brain are completely different entities. The mind is an agent that carries the seed to have the next life. The rūpa is a physical phenomenon. It is the material form of the body and of the eternal world. Earth (prithivi dhātu), water (apo dhātu), fire (tejo dhātu) and wind (vayo dhātu) element are the four fundamental elements in our body and the outer world. Mental phenomenon and physical phenomenon are different but dependents on each other. The objective of this article is to examine the mind and its procedure. Both original texts of Buddhism have been used as primary sources and published books and articles have been used as secondary sources of information. Life is all about the continuous process of mental aggregates and physical matter. The mind links the earlier life to the present and for the future. Suffering and happiness are the two major state of a mind. The worldly mind is the source of suffering whereas the enlightened mind is the source of endless happiness. Buddhism is a way of achieving endless happiness i.e nirvana through the practice of the noble path.